IMPLEMENTATION OF STANDARDIZATION AND CERTIFICATION OF SPORT COMPETENCE - Muhlisin Muhlisin (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2017)
Abstract This study aims to determine the implementation of standardization and certification sports Competencies. Research carried out in several places, namely at the Ministry of Youth and Sports, the office of the Central KONI, and the Office of National Accreditation Institute Sport (LANKOR) This research uses descriptive method. The instrument used is in the form of guidelines for observation, interview and documentation guidelines so that the analysis of data used is descriptive and qualitative analysis. This study concludes that weak management systems implementation of standardization and certification, standardization Synergy implementing agencies, accreditation and certification are still not optimal because the functions and authority of the implementing agencies are still ambiguous. The study also concluded the lack of understanding society sports personality of the implementation of standardization, and certification Competence in sports because it is not supported by a consistent system of accreditation. Keyword : Competence, Sport, standardization, Accreditation, Certification